Effect of Trigonella Foenum – Graceum in Diabetic Albino Wistar Rats and Their Antioxidant Properties - Komal Vishwakarma; Zunjarrao G. Badade; Archana Dhok; Arvind Kushwaha; Ranjit Ambad (Journal of Pharmacy and Bioallied Sciences)
Introduction: The WHO says diabetes is an incurable disease resulting from inadequate amounts of insulin produced by the β-cells of the pancreas or insufficient insulin use by the body. Diabetes mellitus is the 16th top cause of death globally. It is a crucial and significant public health problem. It is broadly recognized that people with diabetes have a higher chance of developing several major complications, like hypertension, hyperlipidemia, and diabetic obesity. Numerous animal models have been created over time to investigate diabetes mellitus or evaluate medications that prevent it. To generate diabetes in these models, several animal species are subjected to pharmacological, surgical (pancreatectomy), and genetic alterations. Aims and Objectives: To study in male Albino Wistar rats the potential anti-oxidant and anti-diabetic effects of fenugreek seeds. Materials and Methods: Male Wistar rats were given streptozotocin to cause diabetes; the rats were subsequently treated with fenugreek seeds. SOD and catalase levels in the serum of Wistar rats were used to determine fenugreek seeds anti-oxidant qualities. Conclusion: Using diabetic Albino Wistar rats, the study revealed Trigonella foenum has anti-diabetic and anti-oxidant qualities.